2017
DOI: 10.1177/1934578x1701201127
|View full text |Cite
|
Sign up to set email alerts
|

Highly Cytotoxic Xanthones from Cratoxylum cochinchinense Collected in Myanmar

Abstract: Eight xanthones and one anthraquinone, together with four common triterpenoids, have been isolated from the barks of Cratoxylum cochinchinense, collected in Myanmar. The structures of the metabolites were elucidated by spectroscopic data analysis and their antiproliferative activities were measured against six human tumor cell lines, by using the MTT assay. Pruniflorone N (1) showed a significant cytotoxicity against all cancer cells with IC 50 values in the range 3-9 µM, on average higher than the anticancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Moreover, the single aromatic proton signal at δ H 7.36 (H-7) (Table 1) revealed in 1 H-NMR spectrum in combination with the correlation of H-7/C-5, H-7/C-8a, and H7/C-4' observed in HMBC spectrum suggested that the hydroxy posited at C-8 (δ C 134.5). Therefore, compound 5 was Additionally, 8 known compounds (Figure 1) were isolated and identified as 1,2,5-trihydroxy-6-methoxyxanthone (1), 7 1,3,6,7-tetrahydroxy-2,5-bis (3-methylbut-2-enyl) xanthen-9one (2), 8 xanthone V1 (3), 9 isojacareubin (4), 10 methyl protocatechuate (6), 11 isoxanthochymol (7), 12 euxanthone (8), 13 and protocatechuic acid (9) 14 through comparison of the spectroscopic data (Supplemental Figures S8-S24) with the corresponding reference data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the single aromatic proton signal at δ H 7.36 (H-7) (Table 1) revealed in 1 H-NMR spectrum in combination with the correlation of H-7/C-5, H-7/C-8a, and H7/C-4' observed in HMBC spectrum suggested that the hydroxy posited at C-8 (δ C 134.5). Therefore, compound 5 was Additionally, 8 known compounds (Figure 1) were isolated and identified as 1,2,5-trihydroxy-6-methoxyxanthone (1), 7 1,3,6,7-tetrahydroxy-2,5-bis (3-methylbut-2-enyl) xanthen-9one (2), 8 xanthone V1 (3), 9 isojacareubin (4), 10 methyl protocatechuate (6), 11 isoxanthochymol (7), 12 euxanthone (8), 13 and protocatechuic acid (9) 14 through comparison of the spectroscopic data (Supplemental Figures S8-S24) with the corresponding reference data.…”
Section: Resultsmentioning
confidence: 99%
“…Fr.7 (1.4 g) was separated by silica gel column chromatography, with chloroform-methanol (1:1, V/V) as the solvent system to obtain 14 components (Fr.7-1 to Fr. [7][8][9][10][11][12][13][14]. Fr.7-10 was fractionated again over silica gel with chloroform-methanol (1:1, V/V) and then further purified by HPLC to obtain compounds 3 (17.3 mg) and 4 (1.0 mg).…”
Section: Extraction and Isolationmentioning
confidence: 99%
“…In our ongoing research on new bioactive constituents from medicinal plants collected in Myanmar [7], a new homoisoflavanone, together with four known congeners and dihydrochalcone (-)-trifasciatine C, were recently isolated from the methanolic extract of S. cylindrica rhizomes [8]. Upon completion of our investigation on this plant, in this paper we describe the isolation and the structure identification of ten additional compounds.…”
Section: Introductionmentioning
confidence: 97%
“…As a part of our investigations of the secondary metabolites from medicinal plants used in Myanmar [5], we have studied, for the first time, the constituents of S. cylindrica rhizomes. We describe the isolation and characterization of a new sappanin-type 3-benzylchroman-4-one (homoisoflavanone) (1), together with four known congeners (2-5), dihydrochalcone 7, stigmasterol, and ergosterol peroxide.…”
mentioning
confidence: 99%
“…-3-(4′hydroxybenzyl)-3,5-dihydroxy-7-methoxy chroman-4-one (4) [9], 3-(3′,4′-methyledioxybenzyl)-7-hydroxy-8-methoxy chroman-4-one (5) [10], 2′,4′-dihydroxy-3′-methoxy-3,4-methylenedioxy-8hydroxymethylene dihydrochalcone (7) [4], stigmasterol, and ergosterol peroxide. Compounds 1-4 have been isolated for the first time from the genus Sansevieria [6], while the structure of compound 5 corresponded to (R)-(-)-trifasciatine A, recently isolated from the aerial parts of S. trifasciata [10].…”
mentioning
confidence: 99%